2018
DOI: 10.1002/adma.201804439
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi‐Solid‐State Flexible Fiber‐Shaped Li–CO2 Battery with Low Overpotential and High Energy Efficiency

Abstract: With the rapidly increasing interests on wearable electronics over the past decades, the limited energy density and nondeformable configuration of conventional 2D lithium-ion batteries (LIBs) have already become the dominant obstacles that are hindering the roads of wearable consumer electronics toward ubiquity. [1][2][3][4][5] Hence, it is urgent to develop an alternative highperformance flexible energy storage device to break through the inherent restrictions of rigid LIBs. [6][7][8] The Li-CO 2 battery, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
247
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(258 citation statements)
references
References 49 publications
(92 reference statements)
6
247
0
Order By: Relevance
“…The C dl was calculated from double-layer charging curves in a non-faradic potential range of 1.1-1.3 V (versus RHE) and using the following equation in which i c and ʋ are charging current (mA cm −2 ) and scan rate (mV s −1 ), respectively [6][7][8][9][10] : The electrocatalytic performances for ORR and OER reactions were measured in a three-electrode cell at standard temperature and pressure conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C dl was calculated from double-layer charging curves in a non-faradic potential range of 1.1-1.3 V (versus RHE) and using the following equation in which i c and ʋ are charging current (mA cm −2 ) and scan rate (mV s −1 ), respectively [6][7][8][9][10] : The electrocatalytic performances for ORR and OER reactions were measured in a three-electrode cell at standard temperature and pressure conditions.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Particularly, Znair batteries (ZABs) with superiorities of high theoretical energy density (1218 Wh kg −1 ), low cost, and high safety possess remarkable potential to meet the increasing practical requirements of flexible and wearable electronics. [1][2][3][4][5][6][7] Particularly, Znair batteries (ZABs) with superiorities of high theoretical energy density (1218 Wh kg −1 ), low cost, and high safety possess remarkable potential to meet the increasing practical requirements of flexible and wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…80 %). [22] Also, its theoretical energy density was far higher than aqueous ZnÀCO 2 batteries and comparable with organic Li(Na)ÀCO 2 batteries (Table S1). Therefore, the reversible hybrid aqueous LiÀCO 2 battery had highenergy conversion and storagep erformance that matcheda nd even exceeded organic LiÀCO 2 batteries and aqueous ZnÀCO 2 batteries in some instances.…”
Section: Resultsmentioning
confidence: 90%
“…Accordingly, ultrathin Ir nanosheets fully anchored on the surface of N‐doped carbon nanofibers (Ir NSs‐CNFs) lowered the charge voltage of the Li–CO 2 batteries to only 3.8 V at 100 mA g −1 and increased the stable cyclability over 400 cycles with a cutoff capacity of 1000 mAh g −1 at 500 mA g −1 . After the successful application of Mo 2 C/CNT catalytic cathodes to significantly lower charge voltage, first‐principles computations further revealed that Mo 2 C could bind oxalate more stably, avoiding the formation of carbonate and carbon derived from oxalate disproportionation . The oxalate product had a charge voltage below 3.5 V, and the Li–CO 2 batteries achieved a high energy efficiency of up to 80% and stable cyclability over 40 cycles at 80 µA cm −2 with 80 µAh cm −2 …”
Section: Individual Development: Energy Storage or Chemical Productionmentioning
confidence: 99%
“…After the successful application of Mo 2 C/CNT catalytic cathodes to significantly lower charge voltage, first‐principles computations further revealed that Mo 2 C could bind oxalate more stably, avoiding the formation of carbonate and carbon derived from oxalate disproportionation . The oxalate product had a charge voltage below 3.5 V, and the Li–CO 2 batteries achieved a high energy efficiency of up to 80% and stable cyclability over 40 cycles at 80 µA cm −2 with 80 µAh cm −2 …”
Section: Individual Development: Energy Storage or Chemical Productionmentioning
confidence: 99%